Beyond the Ousting of Mubarak: An Intersectional Analysis of Egyptian Women's Activism After the 2011 Egyptian Revolution - Zaky, Radamis (Université d'Ottawa / University of Ottawa, 2022)
Egyptian women played an integral and important role in the 2011 Egyptian Revolution. Egypt witnessed different forms of struggles and fights over power since January 25, 2011. The last decade can be understood as episodes of contention. Women played vital roles in each of these episodes. Both the complexity and dynamics of the different roles played by women problematized the various conceptual frameworks that are usually used in analyzing Egyptian women’s various forms of activism. Resultantly, this dissertation suggests a new analytical framework that can be applied to understand Egyptian women’s struggles and ways of expressing their agency. The theory of intersectionality by Collins and Bilge was used to analyze six documentaries produced by either female filmmakers or focused on women’s struggles and activism after the 2011 Egyptian Revolution. The Triple C Model (Context, Contradictions, and Commonalities) analytical framework could fill the analytical gap in understanding the complex discourses surrounding Egyptian women’s oppression and activism.
Keywords: Feminism; Islam; the 2011 Egyptian Revolution; Egyptian Revolution; Violence Against Women; Arabs; Islamic Feminism; Intersectionality